Influence of Ion-Plasma Assistance on the Composition, Structure and Properties of Wear-Resistance Nitride Coatings; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Krysina O. Olga; Shugurov V. V. Vladimir Viktorovich; Prokopenko N. A.; Kovalsky S. S.; Koval N. N. Nikolay Nikolaevich (Ion-Assisted Coating Deposition. Oral Presentation, 2019)
Заглавие с экрана